Arabidopsis thaliana sku mutant seedlings show exaggerated surface-dependent alteration in root growth vector. - Rutherford, R (1996)
Roots of wild-type Arabidopsis thaliana seedlings in the Wassilewskija (WS) and Landsberg erecta (Ler) ecotypes often grow aslant on vertical agar surfaces. Slanted root growth always occurs to the right of the gravity vector when the root is viewed through the agar surface, and is not observed in the Columbia ecotype. Right-slanted root growth is surface-dependent and does not result directly from directional environmental stimuli or gradients in the plane of skewing. We have isolated two partially dominant mutations in WS (sku1 and sku2) that show an exaggerated right-slanting root-growth phenotype on agar surfaces. The right-slanting root-growth phenotype of wild-type and mutant roots is not the result of diagravitropism or of an alteration in root gravitropism. It is accompanied by a left-handed rotation of the root about its axis within the elongation zone, the rate of which positively correlates with the degree of right-slanted curvature. Our data suggest that the right-slanting root growth phenotype results from an endogenous structural asymmetry that expresses itself by a directional root-tip rotation.